A benchmarking framework for eTourism capability of destinations' industries. (12th August 2014) - Reino, Sofia; J. Frew, Andrew; Mitsche, Nicole
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to provide a framework for benchmarking the eTourism capability of a destination's tourism industry, understanding the eTourism capability of a destination's industry as the contribution that the information and communication technologies (ICT) uptake of that industry makes to its own performance. The impact of ICT in tourism has been suggested through extensive research. Previous work has urged the development of wide-angle studies to enable benchmarking of destinations and their industries. However, relevant research is limited. Macro-level studies in the area tend to focus on a single aspect of technology to evaluate adoption, are not sector-specific nor take into consideration the different levels of contribution that systems may bring to performance. Design/methodology/approach – A review of the literature on tourism, eTourism, benchmarking and technology adoption provided the baseline for developing this benchmarking tool. Findings – The literature supported the selection of key tourism industry sectors, i.e. accommodation establishments, visitor attractions and food and beverage; the most suitable methodology, i.e. intermediary performance measures; and the business characteristics that need being taken into consideration when assessing ICT adoption by tourism businesses, e.g. size, type of establishment and area of location. Research limitations/implications – The framework has not been tested yet. It is based on a review of the literature and needs to be validated through primary research. The framework was developed based on the context of Scotland. Further work should be done to adjust the framework to other destinations worldwide. Practical implications – The framework enables destinations to benchmark the eTourism capability of their industries. Originality/value – It provides a comprehensive framework for benchmarking tourism destinations' industries, which takes into consideration elements of technology adoption, the characteristics of the tourism industry and the particularities of the different ICT elements.